In the pages of legal cases: children and teenagers, their voices, leading participation and counter-conduct (Tempo e Argumento, 2022)
This research aims to voice some experiences of the juvenile public found on legal cases in the '90s, to understand how institutionalized children and teenagers dealt with the choices taken by adults, whether they were relatives, shelter counselors, or legal professionals. To reach this goal, the following questions were asked. Which cases were the children and teenagers heard? Who did listen to them? What did the adults do about what they heard? And, when they were not listened to, what did they do? The main idea is to present the children and teenagers' perspective, their actions, strategies, and feelings, and to describe them as historical subjects and social actors of their time. From this perspective, this article was divided into three parts. In the first part, the concept of leading engagement and the relationship between the separate concepts of engagement and leadership were presented. In the second part, the focus was the analysis of the listenning process, where the children and teenagers spoke, and the adults listened; whether at legal hearings or everyday conversations. The last part focus in the refusal to listen, in the choices imposed by the adults, and in the children and teenagers' reactions accordingly to their field of experience and expectative horizon.
Keywords: history of childhood and youth; leading engagement; counter-conduct; legal cases